CONSTRAINTS TO FEMALE LABOR FORCE PARTICIPATION: A SOCIOLOGICAL STUDY OF FEMALE STUDENTS IN HIGHER INSTITUTIONS OF SUKKUR CITY - Razia Sultana Channa; Dr. Nadia Agha; Moomal Mandhri Channa; Amjad Ali Maitlo (International Journal of Contemporary Issues in Social Sciences, 2024)
Women’s labor is essential to Pakistan’s economic growth. This study looks into the barriers Pakistani women experience when trying to enter the workforce. Using a quantitative technique and a sociological approach, the study makes four hypotheses based on a literature review that follows. Data is collected from 252 female students in higher institutions in Sukkur, Sindh, using stratified random sampling and a structured questionnaire. Statistical analyses through SPSS and Excel reveal that entrenched patriarchal norms devalue women’s jobs, perpetuating the notion of men as sole breadwinners, and discouraging women from entering the workforce. Societal pressures and expectations compound the challenges, with Islamic beliefs about Pardah further limiting women’s labor force participation. The stress of balancing home and work responsibilities also emerges as a significant constraint. Educational disparities persist, violating women’s rights and impeding socio-economic progress. Limited mobility, dependence on male family members for transportation, and fear of sexual harassment contribute to reluctance, both by women and their families, to embrace employment opportunities. The findings affirm the proposed hypotheses. To alleviate these constraints, the study recommends government initiatives such as vocational training programs, enhancements to existing centers, family policies supporting working women, public awareness campaigns, and the provision of safe transportation for women. These barriers must be removed if female labor force participation and socioeconomic advancement are to improve.